1997
DOI: 10.1074/jbc.272.8.5256
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Distinct Ryanodine Receptor Mutation in Human Malignant Hyperthermia-susceptible Muscle

Abstract: Malignant hyperthermia is an inherited autosomal disorder of skeletal muscle in which certain volatile anesthetics and depolarizing muscle relaxants trigger an abnormally high release of Ca 2؉ from the intracellular Ca 2؉ store, the sarcoplasmic reticulum. In about 50% of cases, malignant hyperthermia susceptibility is linked to the gene encoding the skeletal muscle ryanodine receptor/Ca 2؉ release channel (RYR1). To date, eight point mutations have been identified in human RYR1. Although these mutations are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 40 publications
(19 reference statements)
5
60
1
Order By: Relevance
“…Richter et al (27) showed that the G2434R mutation identified in patients with MH enhances the sensitivity of RyR1 to Ca 2+ and caffeine. Similar findings were reported by Yang et al (28) when they expressed 6 common RyR1 mutants found in MH patients (R163C, G341R, R614C, R2163C, V2168M, and R2458H) in myotubes differentiated from cells lacking endogenous RyR1, and by Wehner et al (29) when they characterized RyR1 mutants in primary human myotubes cultured from carriers of RyR1 mutations.…”
Section: Ryanodine Receptors and Human Diseasesmentioning
confidence: 99%
“…Richter et al (27) showed that the G2434R mutation identified in patients with MH enhances the sensitivity of RyR1 to Ca 2+ and caffeine. Similar findings were reported by Yang et al (28) when they expressed 6 common RyR1 mutants found in MH patients (R163C, G341R, R614C, R2163C, V2168M, and R2458H) in myotubes differentiated from cells lacking endogenous RyR1, and by Wehner et al (29) when they characterized RyR1 mutants in primary human myotubes cultured from carriers of RyR1 mutations.…”
Section: Ryanodine Receptors and Human Diseasesmentioning
confidence: 99%
“…Other Potential 4-CmC Effector Sites-Point mutations in the MH sensitivity region 2 of wtRyR1 (residues 2129 -2458) can either increase (11,17,18) or decrease (32) 4-CmC sensitivity, thus suggesting that this domain might also contain a potential 4-CmC effector site. However, these mutations also alter sensitivity to other RyR agonists such as caffeine and halothane, thus suggesting a more general effect on RyR activity.…”
Section: Binding Studies and 4-cmc Activation Mechanism-we Conducted [mentioning
confidence: 99%
“…Originally used as a preservative in commercial preparations of some intravenous drugs, including succinylcholine, 4-CmC can directly activate the RyR with 10 -25-fold higher potency compared with the more commonly used RyR activator, caffeine (14 -16). In addition, the sensitivity to activation by 4-CmC is increased for RyR1 channels containing point mutations that have been linked to MH (11,17,18). Indeed, because of its higher potency relative to caffeine, 4-CmC has been recommended as a supplemental test substance in the in vitro contracture test for diagnosing MH in humans (12).…”
mentioning
confidence: 99%
“…Once a causative mutation is found in a family member, others may be tested for susceptibility by seeking out that mutation in the DNA. [67,69], and, indirectly, by protein release [70]. Systems using 1B5 dyspedic myotubes are more physiological as they constitutively express all the components of the skeletal muscle with the exception of RYR1 [67].…”
Section: Laboratory Diagnostic Methodsmentioning
confidence: 99%